External Trigger Factors for Violent Offending: Findings From the U.K. Prisoner Cohort Study - Freestone, Mark C. (Criminal justice and behavior, 2017)
The role of “triggers” for violence is seldom considered when assessing risk of violence in prisoners and forensic patients. A sample of 494 cases from a two-phase study of violent prisoners in England and Wales were rated for presence of acute risk factors and “triggers” occurring before the index offense. Logistic regression was performed to test prediction of acute factors and triggers by preoffense static and stable dynamic factors. Regression models were then built to investigate associations between triggers and violent reoffending post release. Although stable dynamic risk factors were accurately predicted by static actuarial risk, neither were associated with specific violence triggers. An argument with a stranger resulting in violence was associated with future violent reoffending. Violence triggers are highly context-specific but cannot be predicted using existing risk factors. They have a complex relationship with preexisting dynamic factors resulting in future violence.